Early-onset Alzheimer’s disease with depression as the first symptom: a case report with literature review - Liu, Meichen; Xie, Xueting; Xie, Jinghui; Tian, Shiyun; Du, Xuemei; Feng, Hongbo; Zhang, Huimin (Frontiers in Psychiatry, 2023)
Background Alzheimer’s disease is a common neurodegenerative disease, and patients with early-onset Alzheimer’s disease (onset age < 65 years) often have atypical symptoms, which are easily misdiagnosed and missed. Multimodality neuroimaging has become an important diagnostic and follow-up method for AD with its non-invasive and quantitative advantages. Case presentation We report a case of a 59-year-old female with a diagnosis of depression at the age of 50 after a 46-year-old onset and a 9-year follow-up observation, who developed cognitive dysfunction manifested by memory loss and disorientation at the age of 53, and eventually developed dementia. Combined with neuropsychological scales (MMSE and MOCA scores decreased year by year and finally reached the dementia criteria) and the application of multimodal imaging. MRI showed that the hippocampus atrophied year by year and the cerebral cortex was extensively atrophied. 18F-FDG PET image showed hypometabolism in right parietal lobes, bilateral frontal lobes, bilateral joint parieto-temporal areas, and bilateral posterior cingulate glucose metabolism. The 18F-AV45 PET image showed the diagnosis of early-onset Alzheimer’s disease was confirmed by the presence of Aβ deposits in the cerebral cortex. Conclusion Early-onset Alzheimer’s disease, which starts with depression, often has atypical symptoms and is prone to misdiagnosis. The combination of neuropsychological scales and neuroimaging examinations are good screening tools that can better assist in the early diagnosis of Alzheimer’s disease. Graphical Abstract